Pengaruh Rapat Arus Terhadap Ketebalan Dan Struktur Kristal Lapisan Nikel pada Tembaga - Setyowati S; Y Iriani; A H Ramelan (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
The effect of current density on thickness and crystal structures of the coatings in the electroplating of nickel on copper has been investigated. The electroplating of nickel was conducted at a voltage of 0.5 V for 10 minutes with varied current densities of 0.3 mA/cm2; 0.6 mA/cm2; 0.9 mA/cm2; and 1 mA/cm2. The nickel coatings werw tested by thickness measurement and crystal structures determination. The experimental results showed that the thickness of the nickel coatings increased as the current density increased. The XRD characterization of the nickel coatings revealed the diffraction patterns for cubic structures with orientation of (111) and (200). As the current density increases, the crystal with (111) and (200) orientation tends to be formed more lagely.